ASSESSMENT OF THE DEVELOPMENT OF FOLK CRAFTS IN THE REGION BASED ON TREND MODELS - Norgobilova, Feruza (Innovatsion texnologiyalar, 2024)
It is explained by the scientific justification of methodological approaches to the assessment of the role of family entrepreneurship in the development of folk crafts in the region, as well as the possibility of using them to improve the organizational and institutional basis of regulating family entrepreneurship